Older People and Dissatisfaction with Wheelchair Services - John Stewart; Bob Sapey; Leslie Humphreys; Brian Francis; Glenis Donaldson (Scandinavian Journal of Disability Research, 2008)
Britain has experienced an unprecedented increase in wheelchair use during the past two decades. The authors take a social model approach to disability and report on their study in the north-west of England into the social implications of this increase. Qualitative interviews and a large-scale social survey reveal the circumstances of users and their experiences. Building on their descriptive statistics, the authors use latent class analysis to identify from amongst their respondents the characteristics of dissatisfied users of UK National Health Service wheelchair provision: they were more likely to be older, frailer females; and to be living in residential and nursing care homes. Prescribing practices and policy guidelines are analysed to consider how a hierarchy of need is operating to determine wheelchair allocation.